THE QUESTION OF ETHICS AND RESPONSIBILITY IN VIRTUAL REALITY (Eureka Journal of Humanities and Social Research, 2026)
This article examines the problem of ethical norms and responsibility within the context of virtual reality as an emerging socio-technological environment. The study analyzes how immersive digital spaces transform traditional moral frameworks, reshape human behavior, and challenge established notions of accountability. Particular attention is given to the ontological status of virtual actions and their ethical implications in relation to real-world consequences. The research employs a multidisciplinary approach, integrating philosophical analysis, elements of digital ethics, and socio-psychological perspectives. It argues that despite the simulated nature of virtual environments, user actions within these spaces carry significant moral weight due to their impact on individual consciousness, social interaction, and cultural values. The paper also explores issues such as anonymity, identity construction, and the diffusion of responsibility in virtual contexts. As a result, the necessity of developing adaptive ethical standards and regulatory mechanisms for virtual environments is substantiated. The findings contribute to a deeper theoretical understanding of digital ethics and provide a conceptual basis for future research on moral responsibility in technologically mediated realities
Keywords: Virtual reality, digital ethics, moral responsibility, ethical norms, online behavior, identity, anonymity, simulation, cyber ethics, social interaction.